Clinical Applications of Keystone Design Perforator Island Flap: A Single-Center Experience - Georgieva, Gordana; Tusheva, Sofija; Nikolovska, Bisera; Srbov, Blagoja; Dzonov, Boro; Pejkova, Sofija (SciTeMed Publishing Group, 2023)
Objective: The field of microsurgery is constantly striving for innovative reconstructive techniques that offer optimal outcomes. Among these techniques, the keystone design perforator island flap (KDPIF) has emerged as a prominent solution, garnering substantial attention from surgeons worldwide. Its versatility and simplicity make it a preferred choice for soft tissue reconstruction, regardless of the underlying etiology. In this study, we aimed to share our clinical experience and report on the outcomes of the KDPIF reconstruction process, thereby contributing valuable insights to the existing knowledge base. Methods: This retrospective study analyzed 115 adult patients who underwent KDPIF reconstruction at our clinic over a 40-month period. Patients included elective cases of soft tissue malignancies and chronic wounds, as well as emergency cases due to trauma-inflicted wounds. The surgical technique involved meticulous flap planning based on the defect's orientation, adhering to relaxed skin tension lines. Outcome measures included flap survival rate, postoperative complications, donor site morbidity, and scar assessment using the Manchester scar scale. By evaluating these parameters, we aimed to assess the efficacy and safety profile of the KDPIF technique, providing valuable insights into its clinical utility and outcomes. Results: In our study cohort of 115 patients, male individuals constituted 73% of the participants, with an average age of 55.7 years. Notably, our findings unveiled skin malignancies as the prevailing etiology for soft tissue defects. Localization analysis revealed that most defects were situated on the trunk (49.6%), followed by the lower extremity (23.5%). Among the various reconstructive options available, Type II KDPIF emerged as the predominant choice, employed in most cases (n=85), while type IV reconstruction was only required by two patients. Medium-sized defects, ranging from 16 to 50 cm², represented a significant proportion, accounting for 47.8% of cases. Operative procedures exhibited an average duration of 56 minutes, with no significant increase observed for larger defects. Postoperative complications occurred in 13.04% of patients, primarily manifesting as infections and partial flap necrosis, which were predominantly managed conservatively. The average hospital stay was 4.7 days, and at the 6-month follow-up, patients reported no incidences of flap sensitivity issues. Additionally, a mean Manchester scar scale score of 7.8 signified favorable results for the patient cohort. Conclusion: The KDPIF stands out as an efficient reconstructive technique, capable of addressing soft tissue defects in a single surgical procedure. Notably, its simplicity and expediency contribute to its widespread adoption. Our study reinforces the expanding indications for the use of the KDPIF, further emphasizing its clinical significance. The insights garnered from our clinical experience underscore the favorable outcomes associated with this versatile flap, establishing it as a reliable tool in the armamentarium of soft tissue reconstruction. Future research endeavors are warranted to explore and refine the application of the KDPIF in diverse clinical scenarios.
Keywords: KDPIF; keystone flap; microsurgery; perforator flap; soft tissue defects; surgical reconstruction